PENGARUH TEKNIK RELAKSASI TERHADAP PERUBAHAN STATUS MENTAL KLIEN SKIZOFRENIA DI RUMAH SAKIT JIWA DAERAH SURAKARTA - Kustanti, Erviana; Widodo, Arif (Universitas Muhammadiyah Surakarta, 2008)
Background: The complexity and hardly living and the increasing of psychosocial stress maker cause human disable to prevent the pressure of live. Critical condition brings the effect to the increasing of mental emotional disease, and one of them of the increasing of schizophrenia. Target of: The progressive relaxation technique is given to clients of schizophrenia to know the effect of the change of client's mental status. This research is a qualitative research with experimental research by the scheme of pretestposttest research with control group. The characteristic of respondents is clients with schizophrenia hospitality maintenance categorized. There are 16 respondents, research instruments is questionnaire of mental status value formatted, system of psychological categorized and the standard observation instrument of relaxation technique. Data analysis by using U Test of Mann-Whitney statistic test. Based on U Test of Mann-Whitney statistic test is gained significant number P = 0,001 (P < 0,05). It means that the significant different between before and after giving of relaxation technique between behavioral group and controlled group. The are differentiation between before and after the giving of progressive relaxation technique between behavioral group and controlled group on research respondents.